2011
DOI: 10.1007/s11414-011-9258-7
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Evaluation of Associations Between Displayed Depression References on Facebook and Self-reported Depression Using a Clinical Scale

Abstract: The objective of this study was to determine associations between displayed depression symptoms on Facebook and self-reported depression symptoms using a clinical screen. Public Facebook profiles of undergraduates from two universities were examined for displayed depression references. Profiles were categorized as depression symptom displayers or non-displayers. Participants completed an online PHQ-9 depression scale. Analyses examined associations between PHQ-9 score and depression symptom displayers versus n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 29 publications
2
85
5
1
Order By: Relevance
“…Previous work found that approximately a quarter of publicly available Facebook profiles of undergraduates displayed depression symptom references, and a small proportion of profiles displayed depression symptoms in patterns consistent with the Diagnostic and Statistical Manual (DSM-IV) criteria for a major depressive episode (MDE) [4,5]. Additionally, display of depression symptoms was positively associated with reporting depression symptoms using a clinical screen [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work found that approximately a quarter of publicly available Facebook profiles of undergraduates displayed depression symptom references, and a small proportion of profiles displayed depression symptoms in patterns consistent with the Diagnostic and Statistical Manual (DSM-IV) criteria for a major depressive episode (MDE) [4,5]. Additionally, display of depression symptoms was positively associated with reporting depression symptoms using a clinical screen [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies to date have primarily considered how the relative frequency of words indicating positive and negative emotion relate to other characteristics such as mental health status, or which words (or set of words) best predict different outcomes. Such studies have indicated that the frequent expression of negative emotion words in status updates can accurately identify individuals experiencing symptoms of depression [2][3][4][5]. However, an individual's mental health is likely to be reflected by more than just the average frequency or the type of words used; variability in emotional expression over time might also provide significant insights.…”
Section: "With As Much As We Have Learned About Emotions It Is As Ifmentioning
confidence: 99%
“…At a broad level, the frequent expression of negative affect within social media status updates has been associated with higher levels of depression symptoms [2,3,5,[7][8][9][10]. Frequently expressing positive affect, on the other hand, tends to be associated with lower levels of depression and greater levels of well-being [8,11,12].…”
Section: Depression In Status Updates On Social Mediamentioning
confidence: 99%
See 2 more Smart Citations